2016
DOI: 10.1103/physreva.93.060303
|View full text |Cite
|
Sign up to set email alerts
|

Measure-independent freezing of quantum coherence

Abstract: We find that all measures of coherence are frozen for an initial state in a strictly incoherent channel if and only if the relative entropy of coherence is frozen for the state. Our finding reveals the existence of measure-independent freezing of coherence, and provides an entropy-based dynamical condition in which the coherence of an open quantum system is totally unaffected by noise.Quantum coherence is a fundamental feature of quantum mechanics, describing the capability of a quantum state to exhibit quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 48 publications
(86 reference statements)
1
54
0
Order By: Relevance
“…The freezing of coherence means that the coherence of the quantum system (quantified by some coherence measure) is not affected by noise. When the freezing of coherence is independent of the choice of measures, it is called universal freezing [36,37]. Especially, in Ref.…”
Section: Characterizing the Freezing Of Coherencementioning
confidence: 99%
See 2 more Smart Citations
“…The freezing of coherence means that the coherence of the quantum system (quantified by some coherence measure) is not affected by noise. When the freezing of coherence is independent of the choice of measures, it is called universal freezing [36,37]. Especially, in Ref.…”
Section: Characterizing the Freezing Of Coherencementioning
confidence: 99%
“…Especially, in Ref. [37], it is shown that under a strictly incoherent channel, the universal freezing of coherence occurs if and only if the relative entropy of coherence is frozen. This implies that if we can witness the freezing of relative entropy of coherence, we can assure that the coherence of the quantum system is completely unaffected by noise.…”
Section: Characterizing the Freezing Of Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the theoretical [28, 32-35, 37, 38] and experimental [17][18][19][20][21] work has focused on quantum phase transitions (QPTs) that are driven by the strength of the Raman field and are accessible in both pseudospin-1/2 and spin-1 bosons. Interestingly, for polar spin-1 bosons, the phenomena and nematic QPTs that can be evoked by SOC goes beyond transverse field induced transitions, and remains largely unexplored apart from mean field (MF) [35,39] and variational solutions [33,36,40]. Our work aims to fill this gap by developing a field theory description of nematic QPTs.…”
mentioning
confidence: 99%
“…We have considered here, perhaps, the simplest spinor mixtures. This can be naturally extended to mixtures of high spin systems [31][32][33][34][35][36][37], where both the interand intra-species spin-exchange interactions exist, the interplay between which may lead to even richer physics. The system considered here is quasi-one dimensional.…”
mentioning
confidence: 99%